Right-sided massive hemorrhagic pleural effusion with pancreaticopleural fistula secondary to pancreatitis: A rare cause of pediatric respiratory distress - H S Vinayaka; Dhananjaya Sarji Rudrappa; H S Sathish (Wolters Kluwer Medknow Publications, 2020)
Hemorrhagic pleural effusion secondary to pancreaticopleural fistula (PPF) due to acute-on chronic pancreatitis is a very rare cause of pediatric respiratory distress. Hemorrhagic pleural effusion secondary to PPF will be usually left sided and accounts for 1% of all cases; very rarely, it could be right sided resulting in difficulty in establishing the diagnosis if chest symptoms are disproportionately more than the abdominal symptoms. We report a 9-year-old male child who presented to us with severe respiratory distress, with insignificant history later found to have right-sided massive hemorrhagic pleural effusion with PPF secondary to acute-on chronic pancreatitis.